2022
DOI: 10.3389/fphar.2022.827411
|View full text |Cite|
|
Sign up to set email alerts
|

Phytotherapy for Attention Deficit Hyperactivity Disorder (ADHD): A Systematic Review and Meta-analysis

Abstract: Attention deficit hyperactivity disorder (ADHD) is commonly a neurodevelopmental behavioural disorder in children and adolescents. Mainly characterized by symptoms like lack of attention, hyperactivity, and impulsiveness, it can impact the overall mental development of the one affected. Several factors, both genetic and non-genetic, can be responsible for this disorder. Although several traditional treatment methods involve medication and other counselling techniques, they also come with different side effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 75 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…In some RCTs conducted on children and adolescents with ADHD using herbs such as Gingko biloba and Valeriana officinalis, it was reported that such herbs might ameliorate ADHD symptoms [128,129]. However, systematic reviews and meta-analyses assessing the possible effects of herbs on children with ADHD have concluded that available evidence is inconclusive and insufficient to recommend herbs as an alternative treatment for ADHD [130][131][132][133].…”
Section: Applications and Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some RCTs conducted on children and adolescents with ADHD using herbs such as Gingko biloba and Valeriana officinalis, it was reported that such herbs might ameliorate ADHD symptoms [128,129]. However, systematic reviews and meta-analyses assessing the possible effects of herbs on children with ADHD have concluded that available evidence is inconclusive and insufficient to recommend herbs as an alternative treatment for ADHD [130][131][132][133].…”
Section: Applications and Adverse Effectsmentioning
confidence: 99%
“…Despite a number of clinical trials reporting positive effects for different herbs such as the aforementioned, it is fundamental to acknowledge that results should be interpreted with caution, given that their validity and generalizability to the paediatric population are commonly hampered by methodological heterogeneity, lack of long-term follow-ups, small sample sizes and absence of common clinical and objective measurements as concluded in available systematic reviews [130][131][132][133]143]. Further research is needed in this area to address knowledge gaps and establish the efficacy and safety profiles of herbal treatments, thus potentially providing alternative treatment approaches for consideration in clinical practice.…”
Section: Applications and Adverse Effectsmentioning
confidence: 99%
“…In many review articles, specifically EGb 761 ® , rather than “Ginkgo extract” was examined, or the authors carefully distinguished between different extracts (for a few selected examples, see Gauthier and Schlaefke, 2014 ; Barth et al, 2021 ; DeFeudis, 1991 ; Spiegel et al, 2018 ; Tomino et al, 2021 ; Zhang et al, 2016 ; Riepe, 2020 ; Farzaei et al, 2017 ; Müller et al, 2019 ; Hashiguchi et al, 2015 ; Solfrizzi and Panza, 2014 ; Tan et al, 2015 ). In other studies, the distinction was less stringent or not implemented at all (for a few selected examples, see Al-Kuraishy et al, 2022 ; Dutta et al, 2022 ; Zhao et al, 2021 ; Hallak et al, 2021 ; Ibrahim et al, 2021 ). Thus, it may be misleading to generalize evidence gained for one specific extract to all products made from the same plant.…”
Section: Highest Quality: Is It Worth All the Trouble?mentioning
confidence: 99%
“…The prevalence of this disorder is 6.76% in adults and 5% to 7% in children (Fuller-Thomson et al, 2022; Polanczyk et al, 2007; Song et al, 2021; Willcutt, 2012). About 50% of children and adolescents with this disorder maintain their symptoms during adulthood (Dutta et al, 2022; Faraone & Biederman, 2005; Pellow et al, 2011). Attention deficit-hyperactivity disorder (ADHD) is accompanied by numerous issues in personality, psychological and educational fields, including media and internet abuse, a tendency to use drugs, poor academic performance, high-risk sexual behaviors, poor quality sleep, risk of suicide attempts, impulsive and unplanned behaviors, disturbed relations with family and friends, criminal actions, sever anxiety and mood problems in childhood and adolescence (Jia et al, 2021; Thapar & Cooper, 2016).…”
Section: Introductionmentioning
confidence: 99%